Autism Spectrum Disorder: Assessing the level of knowledge and perceived challenges to early diagnosis and intervention among general practitioners in the city of Tripoli, Libya - Jubr, Soad (Department of Paediatrics and Child Health, 2019)
Introduction Autism spectrum disorder (ASD) is an important global health problem. It has been shown that early diagnosis and intervention can improve the outcomes in affected children. Lack of knowledge about ASD among health care practitioners can delay the identification of children with ASD as well as early intervention. Currently, a dearth of epidemiological information exists regarding ASD in Africa. The aim of this study was to assess the knowledge of general practitioners (GPs) in Libya regarding ASD and to identify perceived challenges by GPs to early diagnosis and intervention of children with ASD in Libya. The study included the working GPs in the city of Tripoli. Methodology This cross-sectional descriptive study was conducted between 1st June 2017 to 31st August 2017 and utilized an electronic platform, the Research Electronic Data Capture (REDCap) from the University of Cape Town to collect study information. The Knowledge about Childhood Autism among Healthcare Workers (KCAHW) is validated questionnaire that explores health care worker knowledge about ASD across four domains. The KCAHW was used in combination with a more detailed questionnaire which explored challenges to early identification and interventions by GP’s in Libya. Descriptive statistics are reported in percentages and the Wilcoxon rank sum test was used to explore relationships between domain knowledge scores with age and gender as well as years of experience as a GP. Results The number of surveys returned to the REDCap application survey site was 215 which represent a response rate of 58.1%. However, the number of complete responses which could be included in data analysis was found to be only 62, indicating an overall response rate of 16.7%. The median age of the participants was 30 years old, IQR (29-33) years with a female predominance amongst participants (n= 55, 89%). The total median score from the knowledge questionnaire was 10, IQR (8- 12). No statistical differences could be found between domain knowledge scores and participants' age, gender and work practice. Participants showed good knowledge about stereotypical movements and repetitive behaviours in ASD, but 48% were not aware of comorbidities associated with ASD. The main challenges identified by GPs in the management of ASD were lack of awareness, insufficient experience, and health infrastructure in Libya as well as social stigma associated with developmental disorders. Conclusion and recommendations GPs in Libya have limited knowledge about certain aspects of ASD. A number of challenges were identified by GPs which hamper the early identification and management of ASD in Libya. There is a need to improve undergraduate medical training about ASD as well as to offer ongoing medical education to GP’s to improve recognition and management of ASD in Libya. Further research is indicated to explore the epidemiology, clinical spectrum and severity of ASD as well as intervention in Libya